A review of the necessity of AI application in English education in Chinese colleges and universities - Yuping Shao; Supyan Hussin; Hanita Hanim Ismail (Environment and Social Psychology, 2026)
The integration of Artificial Intelligence (AI) in Chinese universities for the teaching and learning of the English language marks a significant transformation from traditional methods of teaching. It addresses the global demands of communication and places the country on a higher pedestal in the international arena. This paper explores how AI has transformed the teaching and learning of English by improving engagement and modernizing the methods of teaching. This has been done with the help of a number of secondary literatures on the theme. Tools such as chatbots and Intelligent Tutoring Systems have enhanced the vocabulary, pronunciation, and grammar of students. However, AI comes with its own threats. Challenges such as over-dependence on technology and breach of data emphasize the need to use AI consciously. Though AI can never replace humans, its proper utilization guided by educators and policymakers can definitely help enhance the English language learning experience in a country like China.